Band adhesions not related to previous abdominal surgery – A retrospective cohort analysis of risk factors. (December 2018) - Skoglar, Andreas; Gunnarsson, Ulf; Falk, Peter
Abstract: Background: Postoperative intra-abdominal adhesion formation is a common cause of small bowel obstruction (SBO). Adhesions causing SBO are classed as either matted adhesions or solitary band adhesions. The aim of this study was to investigate the prevalence of previous abdominal surgery in a cohort of patients operated for bowel obstruction and to analyze the causes of obstruction discovered at surgery. Materials and methods: The study was performed at a county hospital with a catchment population of 120 000 inhabitants. Records of operations performed for bowel obstruction over a period of 70 months were retrieved. Results: Of the 196 surgical procedures for intestinal obstruction included, 108 (55%) were caused by adhesions. In this group, 42 (39%) were due to solitary band adhesions and 66 (61%) were due to matted adhesions. Ten of 18 male patients (56%) with a solitary obstructing band had not undergone previous abdominal surgery (p < 0.05). In the cohort as a whole, a significant number of surgical procedures were performed for solitary band adhesions in patients without prior history of surgery (p < 0.01). Conclusion: In male patients, not only previous abdominal surgery but also other factors appear to increase the risk for bowel obstruction due to a solitary band. For intestinal obstruction caused by matted adhesions, however, previous abdominal surgery is the main risk factor in both genders. Patients with signs of SBO but without previous abdominal surgery should be managed bearing in mind that solitary band adhesion and thereby strangulation may be present regardless of previous surgery or not. Highlights: Post-operative abdominal adhesions are a common reason for small bowel obstruction. Abdominal adhesions can develop without undergoing previous surgery. Band adhesions occurs without prior surgery – gender seems to be of importance.